Effect of education and muscle relaxation program on anxiety, depression and care burden in caregivers of acute stroke survivors: A randomized, controlled study. Issue 4 (29th January 2021) - Wang, Jinhong; Liu, Jie; Li, Ling; Man, Jing; Yue, Shihong; Liu, Zhaojun
Abstract : Abstract: This study intended to discover the effect of education and muscle relaxation (EMR) program on anxiety, depression and care burden among caregivers of acute stroke survivors. This randomized, controlled study enrolled a total of 110 caregivers of first-ever acute stroke patients, and randomly assigned to EMR (N = 55) and control (N = 55) groups. The caregivers in the EMR group received 12-month health education and progressive muscle relaxation, and those in control group were provided common rehabilitation advices. Hospital Anxiety and Depression Scale (HADS) and Zarit Caregiver Burden Scale in caregivers were evaluated at the time of patients' discharge from hospital (M0), then at month(M) 3, M6 and M12 after the discharge. HADS-anxiety score, anxiety rate and severity were similar at M0, M3, while were reduced at M6 and M12 in EMR group compared to control group. Furthermore, HADS-depression score was similar at M0 and M3 but was decreased at M6 and M12 in EMR group compared with control group, however, there was no difference of depression rate and severity between the 2 groups at each time point. Moreover, Zarit Caregiver Burden Scale score was similar at M0 and M3, but was decreased at M6 and M12; meanwhile, degree of care burden was similar at M0, M3 and M6, but was reduced at M12 in EMR group compared to control group. EMR program decreases anxiety, depression and care burden in caregivers of acute stroke survivors, suggesting its potential in improving mental health and further promoting quality of lives in these caregivers.